2021
DOI: 10.32674/jis.v11is2.3552
|View full text |Cite
|
Sign up to set email alerts
|

Higher Degree Students (HDR) during COVID-19

Abstract: The wellbeing of higher degree research (HDR) students, or postgraduate students during the COVID-19 pandemic has been of concern. In Australia, international students have queued for food parcels, while headlines report stark drops in international enrolments and the financial bottom line of universities. We undertook a pilot study using ethnographic interview methods to understand the lived experiences of current international and domestic HDR students at an Australian university in Melbourne, from June to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…SOBI items are generally phrased negatively (e.g., “I feel left out of things,” “If I died tomorrow‚ very few people would come to my funeral”). While this is inherent to this particular questionnaire, that phrasing might present as more sensitive to the conditions of the global COVID‐19 pandemic (Gomes et al, 2021 ) that was just ongoing when participants were invited to take part in this study study. The COVID‐19 lockdown measures increased loneliness in young adults aged 18−25 (Marchini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SOBI items are generally phrased negatively (e.g., “I feel left out of things,” “If I died tomorrow‚ very few people would come to my funeral”). While this is inherent to this particular questionnaire, that phrasing might present as more sensitive to the conditions of the global COVID‐19 pandemic (Gomes et al, 2021 ) that was just ongoing when participants were invited to take part in this study study. The COVID‐19 lockdown measures increased loneliness in young adults aged 18−25 (Marchini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the earliest published studies with a focus on COVID-19 have investigated the impact of the pandemic on students' mental health and well-being. The measures imposed, especially the ban on public and private events, and the closing of shops, restaurants, bars, and entertainment and leisure facilities, could prove to be stressors for students in general, including SA students, potentially resulting in elevated levels of feelings of loneliness, social isolation, anxiety, stress, and depressive symptoms (Elmer et al, 2020;Gomes et al, 2021).…”
Section: 3mentioning
confidence: 99%
“…Similarly, the longitudinal study of 162 Belgian high school exchange students by Geeraert et al (2014) indicated that, over time, students who failed to make friendships with host students experienced higher levels of stress. The studies by Moglen (2017) and Gomes et al (2021) indicate that this psycho-social support is not dependent on a sizeable network of local friends but can also be provided by a network based on shared experiences with international and co-national friends. Gomes et al (2021) also suggested that social networks helped to cope with the stress and challenges induced by the COVID-19 pandemic.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, that is not a proof of my commitment. Gomes et al (2021) describe some of the strategies that are critical to support international students and their capacity to resilience, some of them are engaging with peers, supervisors or the university. Those have not been critical supporting strategies for me.…”
Section: A Tsunami Called Covid-19mentioning
confidence: 99%